Design and Evaluation of a GUI-Based GPA Tracker System Using Python and Sqlite for Student Academic Record Management (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
compute student academic records efficiently. Manual recording of student grades often results in errors, misplaced records, and time-consuming computations, especially when handling multiple students. To address these concerns, the proposed system was developed using Python, Tkinter/CustomTkinter for the graphical user interface, and SQLite3 for database management. The system allows users to add, edit, search, delete, and view student records while automatically computing the Grade Point Average (GPA) based on encoded grades and subject units. Input validation was also integrated to prevent incomplete entries, invalid grades, duplicate student IDs, and other common recording errors. The results of the system testing showed that the GPA Tracker successfully performed its intended functions, including accurate GPA computation, record storage, data retrieval, report generation, and error handling. Overall, the system provides a more organized, accurate, and user-friendly approach to managing student academic records compared to manual methods. This project may also serve as a practical reference for future developers and students studying GUI design, database integration, and academic record management systems.